2016
DOI: 10.1186/s12885-016-2225-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-vascular effects of the cytosolic phospholipase A2 inhibitor AVX235 in a patient-derived basal-like breast cancer model

Abstract: BackgroundGroup IVA cytosolic phospholipase A2 (cPLA2α) plays an important role in tumorigenesis and angiogenesis. It is overexpressed in basal-like breast cancer (BLBC), which is aggressive and usually triple-negative, making it unresponsive to current targeted therapies. Here, we evaluated the anti-angiogenic effects of a specific cPLA2α inhibitor, AVX235, in a patient-derived triple-negative BLBC model.MethodsMice bearing orthotopic xenografts received i.p. injections of AVX235 or DMSO vehicle daily for 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
0
30
1
Order By: Relevance
“…This inhibitor exhibited in vivo anti-inflammatory effects comparable to the reference drugs methotrexate and Enbrel in a prophylactic and in a therapeutic collagen-induced arthritis model, respectively. More recently, the anti-angiogenic effects of this inhibitor, in a patient-derived triple-negative basal-like breast cancer model was evaluated and significant tumor growth inhibition was observed after 8 days of treatment [22]. Decreased endothelial cell proliferation and fewer immature vessels in treated tumors were shown by histology.…”
Section: Inhibitors Of Cytosolic Phospholipase Amentioning
confidence: 99%
“…This inhibitor exhibited in vivo anti-inflammatory effects comparable to the reference drugs methotrexate and Enbrel in a prophylactic and in a therapeutic collagen-induced arthritis model, respectively. More recently, the anti-angiogenic effects of this inhibitor, in a patient-derived triple-negative basal-like breast cancer model was evaluated and significant tumor growth inhibition was observed after 8 days of treatment [22]. Decreased endothelial cell proliferation and fewer immature vessels in treated tumors were shown by histology.…”
Section: Inhibitors Of Cytosolic Phospholipase Amentioning
confidence: 99%
“…Thus as part of our efforts to develop cPLA 2 inhibitors as potential drug candidates for the treatment of neurological disorders, we have synthesized a new series of AA analogues 1 – 2 and evaluated them for their PLA 2 inhibitory activities and ability to cross the BBB. In our inhibitor design, we have focused on the arachidonyl scaffold as earlier studies have shown that this pharmacophore is strongly recognized by cPLA 2 19 23 . We herein present the synthesis of AA analogues 1 – 2 and the investigation of these compounds for their (i) inhibition of cPLA 2 , (ii) cytotoxicity, (iii) selectivity and anti-neuroinflammatory properties and (iv) ability to cross the blood-brain barrier; finally computational studies were performed to understand how the compounds bind to cPLA 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The resolutions listed in this table are for demonstrated breast imaging applications and do not necessarily reflect the capability of the modality in other applications. All modalities have been combined and validated with qualitative histopathology, and many with 2-D quantitative histopathology, so these combinations were not included in the 84 FMT, 85 OCT, 70 μ PET, 86 μ SPECT, 87 MRI, 17 US, radiography, PAT 88 SPC-μCT 100 89,c Advanced μCT has been demonstrated on mastectomy samples, but not non-invasively with patients.…”
Section: Microcomputed Tomographymentioning
confidence: 99%
“…Preclinical μCT has already been paired with many other imaging modalities for QMIB over a wide range of biomedical applications ( Table 3). Some examples include characterizing the biodynamics of molecular imaging agents, 83,86,87,117,118 the biological effects of therapeutic interventions, 84,[119][120][121][122] rapid ex vivo IMA on resected tumors or tumor morphology analysis, [57][58][59]123,124 and the study of vasculature and angiogenesis. 17,84,120,122,125 There is still much room to expand the preclinical applications of this technology.…”
Section: Microcomputed Tomographymentioning
confidence: 99%
See 1 more Smart Citation